Muscle power and fiber characteristics following 8 weeks of plyometric training - Potteiger, J. A.; Lockwood, R. H.; Haub, M. D.; Dolezal, B. A.; Almuzaini, K. S.; Schroeder, J. M.; Zebas, C. J. (The Journal of Strength and Conditioning Research, 1999)
We examined changes in muscle power output and fiber characteristics following a 3 d·wk1, 8-week plyometric and aerobic exercise program. Male subjects (n = 19) were randomly assigned to either group 1 (plyometric training) or group 2 (plyometric training and aerobic exercise). The plyometric training consisted of vertical jumping, bounding, and depth jumping. Aerobic exercise (at 70% maximum heart rate) was performed for 20 minutes immediately following the plyometric workouts. Muscle biopsy specimens were collected from the musculus vastus lateralis before and after training. Type I and type II fibers were identified and cross-sectional areas calculated. Peak muscle power output, measured using a countermovement vertical jump, significantly increased from pretraining to osttraining for group 1 (2.8%) and group 2 (2.5%). Each group demonstrated a significant increase in fiber area from pretraining to posttraining for type I (group 1, 4.4%; group 2, 6.1%) and type II (group 1, 7.8%; group 2, 6.8%) fibers, but there were no differences between the groups. Following plyometric training, there is an increased power output that may in part be related to muscle fiber size.